Activation of a non-eruptive well by using gas lift method and step-up of its productivity: sensitivity and economical analysis. (23rd November 2022) - Matateyou, Josephine Fleur; Karga, Lionel Tapsia; Nitcheu, Madeleine; Kom, Ornella Gwladys Djouwa; Ngueyep, Luc Leroy Mambou; Kingni, Sifeu Takougang
This paper aims to design a gas lift that not only activates a non-eruptive well but also and above all, optimises the recovery of hydrocarbons at the surface while using a very less and limited gas quantity per day. The data are reservoir data, fluid data, well architecture properties, and also injection targets. To achieve the objective, it is necessary to carry out a nodal analysis of the non-eruptive well, and design the gas lift system by finding the gas injection pressure in the well, the number of valves, the optimal heights of injection, and the flow rates received by each valve. The evaluation of the system performance, as well as the sensitivity analysis, allows the selection of an optimal production rate. All the simulation operations and the well diagram are carried out with PIPESIM 2017.1. The results obtained show for the continuous injection of gas at 0.73 and 0.23 mmscf/d respectively. For valves 1 and 2 in the well, i.e., 1 mmscf/d for the two valves and using pressure at the head of the well of 100 psia, an optimal flow rate of 262.9 STB/d can be produced and the payback period is one year and two months.